Analisis Efektivitas dan Efisiensi Sistem Pengelolaan Retribusi Parkir Di Tepi Jalan Umum Di Kota Ambon. - Hutubessy, Eline Octaviana (Fakultas Ekonomi Universitas Wisnuwardhana, 2013)
The aim of the study was to investigate the effect of effectiveness and efficiency on parking retribution in Ambon town.The study was conducted at twelve side street parking lost in Ambon town for tow weeks. The data were collected through observation, interview,and documentation, and analyzed qualitatively. The results of the study indicate that parking retribution at the twelve side street parking lost from 2005-2010 had never reacher the target. The realization was on the average only 50%-54,95% and contribution to the regional original revenue was only 0,76% annually. In product sharing the parther receives 80% and the communication Agency only gest 20% the managemen system of the parking lot is similar for all motor vehicles that is Rp.1000,00 per vehicle and therefore, the distribution realization is very small. The Communication Agency has no ideal parking charge and it makes the parking retribution ineffective and inefficient. In fact the contribution of parking retribution should be Rp 545,240.000,00 with the parking service Rp. 1000,00 per vehicle. The ideal parking charge for a four-wheel vehicle is Rp.3000,00 per vehicle and motor cycle Rp. 2000,00,- By this charge using 38 parking attendants at 12 side street parking lost, the management system will be effective and efficient, The total net realization after realization after reducing the cost for parking attendants is Rp 409,001,750,00 per year and it exceed the target 236%.Kata Kunci: Pengolahan Retribusi Parkir